Pengaruh Pendidikan Kesehatan Remaja Melalui Media Video Terhadap Pengetahuan Siswa Tentang Dampak Seks Bebas - Chelsea Titis Mentari Siwi; J. Nugrahaningtyas W. Utami; Tutik Astuti (SEAJOM: The Southeast Asia Journal of Midwifery, 2019)
Nowadays, many teenagers are faced with various challenges related to sexuality, such as the case of adolescent pregnancy enhancement, and high levels of sexually transmitted diseases (IMS) such as HIV/AIDS. This is hard for the teenagers to avoid because of several factors, such as the development of a child who is looking for a personal identity and always wants to try new things in their environment. The purpose of this research is to know the influence of adolescents ' health education through video media to change students ' knowledge of adolescent free sex impact in one of the high schools in Jogyakarta. This type of research is pre-experimented with a research plan of one group Pretests postest. The number of respondents was 97 students using total sampling technique. Bivariate analysis of the statistics of Wilcoxon, with an error rate of 5% (0.05). Most of the knowledge of respondents was pre Test 69 (71.1%), and post Test 61 (92.4%). The average level of knowledge of respondents pre test mean = 77.53 and the knowledge level respondent post test mean = 89.77 with the significance value of knowledge variable 0.000 (P value < 0.05) (α). There is a health education influence through video media to student knowledge about the impact of adolescent free sex age.